Speed of Light in Hollow-Core Photonic Bandgap Fiber Approaching That in Vacuum - Xiaolu Cao; Mingming Luo; Jianfei Liu; Jie Ma; Yundong Hao; Yange Liu (Sensors)
A Fresnel mirror is introduced at a hollow-core photonic bandgap fiber end by fusion splicing a short single-mode fiber segment, to reflect the light backward to an optical frequency domain reflectometry. The backward Fresnel reflection is used as a probe light to achieve light speed measurement with a high resolution and a high signal-to-noise ratio. Thus, its group velocity is obtained with the round-trip time delay as well as the beat frequency at the reflection peak. Multiple Fresnel peaks are observed from 2180.00 Hz to 13,988.75 Hz, corresponding to fusion-spliced hollow-core fiber segments with different lengths from 0.2595 m to 1.6678 m, respectively. The speed of light in the air guidance is calculated at 2.9753 × 108 m/s, approaching that in vacuum, which is also in good agreement with 2.9672 × 108 m/s given by the numerical analysis with an uncertainty of 10−3. Our demonstration promises a key to hollow-core waveguide characterization for future wide-bandwidth and low-latency optical communication.